JiangyaTongluo decoction ameliorates tubulointerstitial fibrosis via regulating the SIRT1/PGC-1α/mitophagy axis in hypertensive nephropathy - Zhao, Yun; Jia, Qi; Hao, Gaimei; Han, Lin; Gao, Yushan; Zhang, Xiaoyu; Yan, Ziming; Li, Boyang; Wu, Yiping; Zhang, Boya; Li, Yubo; Qin, Jianguo (Frontiers in Pharmacology, 2024)
IntroductionWith the increasing prevalence of hypertension, the incidence of kidney diseases is also increasing, resulting in a serious public burden. Jiangya Tongluo decoction (JYTL), a recognized prescription in traditional Chinese medicine (TCM), is commonly used to calm an overactive liver and reduce excess yang, while also promoting blood flow to alleviate obstructions in the meridians. Previous research has indicated that JYTL may help mitigate kidney damage caused by hypertension; however, the underlying mechanisms have not been thoroughly assessed.MethodsFirst, an amalgamation of UPLC-QE/MS and network pharmacology techniques was employed to pinpoint potential active components, primary targets, and crucial action mechanisms of JYTL in treating hypertensive nephropathy (HN). Then, we used spontaneous hypertensive rats (SHRs) and Wistar-Kyoto rats (WKYs) to evaluate the efficacy of JYTL on HN with valsartan as a positive reference. We also conducted DCFH-DA fluorescence staining in rat renal tissues to detect the level of ROS. Western blotting and immunohistochemistry were performed to investigate further the effect of JYTL decoction on key targets and signaling pathways.ResultsThrough UPLC-QE/MS and network analysis, 189 active ingredients and 5 hub targets were identified from JYTL. GSEA in the MitoCarta3.0 database and PPI network analysis revealed that JYTL predominantly engages in the Sirt1-mitophagy signaling pathway. Tanshinone iia, quercetin, and adenosine in JYTL are the main active ingredients for treating HN. In vivo validation showed that JYTL decoction could improve kidney function, ameliorate tubulointerstitial fibrosis (TIF), and improve mitochondrial function by inhibiting ROS production and regulating mitochondrial dynamics in SHRs. JYTL treatment could also increase the expression of SIRT1, PGC-1α, Nrf1, and TFAM, and activate PINK1/Parkin-mediated mitophagy.ConclusionJYTL decoction may exert renal function protective and anti-fibrosis effects in HN by ameliorating mitochondrial function and regulating the SIRT1/PGC-1α-mitophagy pathway.